Compositional variations in organic acids of selected local fruits at different maturity stages - Lee, Ee Ven (2014)
Selected organic acids were analyzed in Magnifera indica L. chok anan(mango chok anan), Baccaureamotleyanahook.f(Rambai), and Salacca zalacca (Salak) fruits at different maturity stages by HPLC. The M. indica L. chok anan contained malic acid and citric acid in the range of 43.897- 73.396mg/100g FW and 2.681-18.428mg/100g FW at young to ripe stages, respectively. B. motleyanahook.fcontained citric acid and tartaric acid in the range of 4.649-6.114mg/100g FW and 3.645-4.365mg/100g FW at young to ripe stages, respectively. S. zalacca contained malic acid and citric acid in the range of 4.270-17.926mg/100g FW and 0.845-3.284mg/100g FW at young to ripe stages, respectively. Malic acid is the predominant organic acid in M. indica L. chok anan and S. zalacca, while citric acid is the predominant organic acid in B. motleyanahook.f. The tested fruits mostly showed a decrease in the concentration of organic acids with ripening.